Public Value Creation by Private Sector through Cross-Sector Collaboration: A Case Study of the Gojek Wirausaha Program - Kurniawati, Iin; Kustulasari, Agustina (UI Scholars Hub, 2020)
Social reality that is always dynamic in practice often causes the